Mobile Manipulation, Tool Use, and Intuitive Interaction for Cognitive Service Robot Cosero - Stückler, Jörg; Schwarz, Max; Behnke, Sven (Frontiers in Robotics and AI, 2016)
Cognitive service robots that shall assist persons in need in performing their activities of daily living have recently received much attention in robotics research. Such robots require a vast set of control and perception capabilities to provide useful assistance through mobile manipulation and human-robot interaction. In this article, we present hardware design, perception, and control methods for our cognitive service robot Cosero. We complement autonomous capabilities with handheld teleoperation interfaces on three levels of autonomy. The robot demonstrated various advanced skills, including the use of tools. With our robot we participated in the annual international RoboCup@Home competitions, winning them three times in a row.